Hip Displacement Does Not Change After Pelvic Obliquity Correction During Spinal Fusion in Children With Cerebral Palsy. Issue 2 (15th February 2023) - Asma, Ali; Cobanoglu, Mutlu; Ulusaloglu, Armagan Can; Rogers, Kenneth J.; Miller, Freeman; Howard, Jason J.; Shah, Suken A.; Shrader, M. Wade
Abstract : Background: Children with cerebral palsy (CP) frequently develop both neuromuscular hip dysplasia and scoliosis, and occasionally, the timing of the worsening of both of these pathologies is concurrent. The question as to whether the hip or spine should be addressed first in CP remains controversial, with the majority of evidence being "expert opinion." The purpose of this project was to determine the impact of posterior spinal fusion (PSF) on the change in hip displacement for children with CP without previous reconstructive hip surgery. Methods: This was an Institutional Review Board-approved study that observed 67 patients from 2004 to 2018. Inclusion criteria included children with CP, 18 years of age and younger, Gross Motor Function Classification System IV and V, undergoing PSF at a single tertiary care children's hospital with a minimum 2-year follow-up. The primary outcome was the change in hip displacement as quantified by the migration percentage (MP). The hip with the highest MP (worst hip) at the spine preoperative analysis were included for analysis. Triradiate cartilage (TRC) status and pelvic obliquity correction were analyzed with multivariate analysis. Results: Sixty-seven patients were included for analysis, with a mean age of 12.5±2.3 years. The mean major curve angle of the major curve was 77±23 degrees and the mean preoperative pelvic obliquity was 21±12 degrees. There was no statistically significant change in MP after PSF from a mean preoperative value of 41±27%, to a mean postoperative value of 41±29% at the last follow-up, ( P =0.76) The mean follow-up time was 4.1±2.7 years. TRC status ( P =0.52) and the severity of pelvic obliquity ( P =0.10) did not statistically impact the change in MP after PSF. Conclusion: PSF did not influence—either negatively or positively—the progression of hip displacement in children with CP, regardless of pelvic obliquity correction or TRC status. The lack of deterioration in hip displacement post-PSF, however, may suggest a protective effect of spine surgery. Level of Evidence: Level III—retrospective cohort study.